Polyoxovanadate-based organic–inorganic hybrids: from V5O9Cl clusters to nanosized octahedral cages. Issue 9 (4th February 2016) - Zhang, Yu-Teng; Wang, Xin-Long; Zhou, En-Long; Wu, Xue-Song; Song, Bai-Qiao; Shao, Kui-Zhan; Su, Zhong-Min
Abstract : Three nanosized polyoxovanadate-based metal–organic polyhedra have been successfully synthesized, which adopt isostructural octahedral cage geometries. Abstract : Three polyoxovanadate-based metal–organic polyhedra (denoted asVMOP-1, -2, and-3 ), adopting isostructural discrete octahedral cage geometries, were successfully synthesized under solvothermal conditions. These structures are all built up from the same pentavanadate V5 O9 Cl cluster connected by linear bidentate ligands (H2 L1 = H2 BDC, H2 L2 = H2 BDC-NH2, H2 L3 = H2 BDC-Br), respectively.